Socioeconomic inequality, health inequity and well-being of transgender people during the COVID-19 pandemic in Nigeria - Morenike Oluwatoyin Folayan; Anna Yakusik; Amaka Enemo; Aaron Sunday; Amira Muhammad; Hasiya Yunusa Nyako; Rilwan Mohammed Abdullah; Henry Okiwu; Erik Lamontagne (BMC, 2023)
Abstract Background We aimed to explore socioeconomic inequality, health inequity, and the well-being of transgender people during the COVID-19 crisis in Nigeria. Methods Between June and December 2021, a cross-sectional survey was conducted collaboratively with community-based organisations in Nigeria. Participants living with or at risk of HIV were recruited voluntarily, online and face-to-face, using a combination of venue-based and snowball sampling. We assessed the association between gender identity (transgender and vulnerable cisgender women), and (i) socioeconomic inequality measured with socioeconomic status, social status, economic vulnerability, macrosocial vulnerability; (ii) health inequity measured with self-assessment of health, recency of HIV test, access to HIV and sexual and reproductive health services, gender-affirming care, financial and non-financial barriers to accessing health services; and (iii) well-being, measured with gender-based violence, mental health, psychoeconomic preferences. We used multivariable logistic regressions and controlled for interactions and confounders. Results There were 4072 participants; 62% were under 30, and 47% reported living with HIV. One in ten (11.9%; n = 485) was transgender, and 56.5% reported living with HIV. Compared to vulnerable cisgender women, the results showed significantly higher odds (aOR:3.80) of disruption in accessing HIV services in transgender participants; gender-based violence (aOR:2.63); severe (aOR:2.28) symptoms of anxiety and depression. Among the barriers to accessing health and HIV services, transgender had three-time higher odds of reporting additional non-official fees compared to vulnerable cisgender women. The disclosure of their gender identity or sexual orientation was the most important non-financial barrier to accessing health services (aOR:3.16). Transgender participants faced higher housing insecurity (aOR: 1.35) and lower odds of using drugs (aOR:0.48). Importantly, they are more likely to have performed a recent HIV test and less likely to not know their HIV status (aOR:0.38) compared to vulnerable cisgender women. Conclusions Socioeconomic inequality, health and well-being inequity in transgender people appear to be exacerbated by the COVID-19 pandemic in Nigeria. Interventions are necessary to mitigate socioeconomic challenges, address structural inequality, and ensure equitable access to health services to meet the Sustainable Development Goals for transgender people.